2011
DOI: 10.1021/ja2056159
|View full text |Cite
|
Sign up to set email alerts
|

New Electrophilic Addition of α-Diazoesters with Ketones for Enantioselective C–N Bond Formation

Abstract: α-Diazoesters were discovered to be good electrophiles in a catalytic asymmetric α-functionalization of ketones for the first time. This reaction also provided a direct and efficient method for C-N bond formation with excellent yields (up to 98%) and enantioselectivities (up to 99% ee) under mild conditions. The application of the electrophilicity of α-diazoesters opens up a novel way to access the diversity of diazo chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 36 publications
0
68
0
Order By: Relevance
“…Zirconacyclobutene-silacyclobutene complex 1-20 features the concomitance of two Zr-C bonds and two Si-C bonds as well as two fused 4-membered metallacycles, which are useful for further reaction chemistry and synthetic application [45][46][47][48][49][50][51][52]. In 1995, Takahashi and coworkers reported the reaction of bis(alkynyl) silanes with Cp 2 Zr(II) species (Scheme 1.13).…”
Section: Zirconocene-mediated Intramolecular Cyclization Of Bis(alkynmentioning
confidence: 99%
See 3 more Smart Citations
“…Zirconacyclobutene-silacyclobutene complex 1-20 features the concomitance of two Zr-C bonds and two Si-C bonds as well as two fused 4-membered metallacycles, which are useful for further reaction chemistry and synthetic application [45][46][47][48][49][50][51][52]. In 1995, Takahashi and coworkers reported the reaction of bis(alkynyl) silanes with Cp 2 Zr(II) species (Scheme 1.13).…”
Section: Zirconocene-mediated Intramolecular Cyclization Of Bis(alkynmentioning
confidence: 99%
“…When 1-trimethylsilyl-1-propyne was used, only zirconacyclopentadiene 1-43b was isolated regioselectively, and the corresponding zirconacyclohexadiene complex was not isolated (Scheme 1.21) [47,48]. However, further mechanistic study demonstrated that 1-41 was not formed through direct insertion pathway.…”
Section: Reaction Of Zirconacyclobutene-silacyclobutene Complexes Witmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Among various methods for the synthesis of amines, hydrazines often appear as key intermediates. [2][3][4][5][6][7][8][9][10][11][12] Remarkable examples are the addition of alkylzinc reagent to arylazo tosylates, 12 electrophilic addition of -diazoesters with ketones, 13 the addition of carbon nucleophiles to azodicarboxylates 14 and acylhydrazonium salts, 15 the anionic 8,16 or radical 17 additions to the C=N bond of hydrazones, the cross-coupling of ketones with hydrazones, 18 the addition of N-aminolactams to Michael acceptors, 10,19 the aza-Michael addition of hydrazines to electrophilic alkenes, 20 the radical cyclization of N-allyl--perchlorohydrazides, 21 and the 1,3-dipolar cycloaddition of azomethine imines to dipolarophiles. 22 These examples clearly show the significance of N,N bond cleavage in organic synthesis.…”
Section: Introductionmentioning
confidence: 99%